Consumer Perspectives on Luxury Housing Marketing: Validation of a Comprehensive Model in Shiraz - Babaei, Mehdi; Askari, Ahmad; Jamshidi, Dariush (Future of Work and Digital Management Journal, 2025)
The objective of this study was to identify and validate the key factors influencing luxury housing marketing from the consumer’s perspective in Shiraz. This research adopted a quantitative, applied, and descriptive–analytical design. Data were collected through both library and field methods, with the fieldwork conducted using a structured questionnaire developed from the dimensions identified in prior studies. The sample comprised consumers of luxury housing in Shiraz. Descriptive statistics were applied to analyze demographic characteristics, while inferential analyses included the Kolmogorov–Smirnov test for normality, confirmatory factor analysis, linear regression, and structural equation modeling using the partial least squares (PLS) approach. Reliability was assessed through Cronbach’s alpha, and model fit was evaluated using SRMR and NFI indices. The results confirmed the significance of 11 dimensions—technical, physical, building-related, appearance, marketing, environmental, facilities, service, economic, cultural, and locational factors—each demonstrating Cronbach’s alpha values above 0.7, indicating strong reliability. Appearance factors, especially aesthetic view, recorded the highest regression coefficients, followed by technical and locational variables. Marketing dimensions such as branding and social networks were also highly significant, underscoring the growing role of digital engagement. Environmental, facilities, and service-related variables, though comparatively weaker, remained statistically significant at the 95% confidence level. Overall, all constructs in the model were validated, and SRMR and NFI indices indicated acceptable model fit. The study demonstrates that luxury housing marketing is a multidimensional process requiring integration of technical quality, design aesthetics, location, cultural context, and digital marketing strategies. The findings provide a comprehensive framework that can guide developers, marketers, and policymakers in aligning housing projects with consumer expectations in Shiraz and similar urban contexts.